OIL-IN-WATER ANALYZER USING ELECTRICAL CAPACITANCE TOMOGRAPHY (ECT) - LYE , SUET YENG (2009)
Electrical Capacitance Tomography (ECT) is a non-intrusive measurement technique. It visualizes the phase distribution in closed pipes or vessels by measuring the variations in the dielectric properties of materials in within. Dielectric constant (Er) measured is the main concern in determining the type of material. The objective of this project is to develop ECT sensors and evaluate performance of different sensor designs. Capacitance sensors are designed and simulated using COMSOL software. COMSOL simulation gives a visualization of the potential distribution within the measuring area. Four types of sensor designs - with radial screen, without radial screen, internal electrodes and external electrodes sensors are simulated. Next, two types of sensors are fabricated - sensor with internal and external electrodes. The capacitance sensors are calibrated and experimented with various oil-in-water distributions. Data is obtained through the ITS M3000 multi-modal data acquisition unit and computer with M3000 software. Simulation results show that sensor with radial screen and sensor with internal electrodes perform better. Meanwhile, experimental results show both internal and external electrodes sensor designs are capable in visualizing static and dynamic oil-in-water distribution. As a conclusion, designed sensors are able to provide visualization of oil-in-water. Approximate visualization is achieved but image reconstructed do not show the exact oil-in-water distribution.